Influential Factors in the Realization of the Third Place in Informal and Sociable Urban Spaces (Case Study: Informal Sitting Spaces Inside Tehran's Cultural and Commercial Complexes) - Maryam Mohammadi Salek; Ali Asgari (توسعه پایدار شهری)
Problem statement: The reduction of modern human living space, the obliteration of old neighborhoods and their centers, and the large-scale areas inherited from the modern time have reduced sustainable social interactions and the active presence of people in modern cities. Consequently, it seems essential to generate spaces to answer the need for collaboration and thriving of community members and to create attachment and the emergence of a sense of place. So, large-scale urban spaces such as cultural and commercial complexes, which act as semi-public spaces, are responsible for offering such a platform. This issue can be associated with the idea of the third place in urban theorizing on a broad scale, which can be generalized to the bounds of architectural space. Research objective: Therefore, with the aim of improving the quality of informal spaces in large-scale urban buildings and homogeneous densely populated areas, this research tries to investigate the realization of this prominence in the closed and non-public physical spaces of the city by studying the factors affecting the strengthening of the place. Research methods: The current research with its exploratory nature, based on the theoretical background and survey data in a structure consists of three sections: documentary content analysis, Delphi survey, and questionnaire processing using the factor analysis method, aims to identify a meaningful mental pattern in the design process and present a strategy for adapting architecture to the needs of the place. Findings and conclusions: The results of the research questionnaires and their compatibility with the selected research experts’ theoretical opinions indicate a significant relationship between the increase in sociability and the sense of place in informal sitting spaces in cultural and commercial complexes in Tehran. The dimensions of this issue are not restricted to the physical quantity. The functional, structural, cultural, social, and management components can also increase the sense of satisfaction, reconciliation, and invitingness and increase the space's flexibility.